Why foreclosed housing devalues in China? An evaluation based on property-rights risks through hedonic pricing model - Xingyu Qian (Ain Shams Engineering Journal, 2024)
The judicial auction is the sole approach to address foreclosed housing in China. Recently, the pervasive devaluation of foreclosed properties in many cities has become an alarming trend, given its potential to trigger a debt crisis in China's housing system. However, scant research has delved into the reasons why foreclosed properties tend to devalue in comparison to second-hand properties under comparable circumstances. This inquiry scrutinizes three types of property-rights risks in judicial auctions, namely cost risk, acquisition risk, and usufruct risk, using the hedonic pricing model. The results indicate that property-rights risks can dampen homebuyers' willingness to pay, as evidenced by the depreciation of the initial auction price. Nonetheless, credible commitments offered by courts can effectively alleviate property-rights risks, particularly for high-risk properties such as small-property-rights housing or illegal housing, whose transactions are heavily reliant on the courts' credibility.